The Role of the OECD and EU Conventions in Combating Bribery of Foreign Public Officials - Pacini, Carl (Journal of business ethics, 2002)
The OECD Convention on Combating Bribery of Foreign Public Officials in International Business Transactions (the OECD Convention) obligates signatory nations to make bribery of foreign public officials a criminal act on an extraterritorial basis. The purposes of this article are to describe the nature and consequences of bribery, outline the major provisions of the OECD Convention, and analyze its role in promoting transparency and accountability in international business. While the OECD Convention is not expected to totally eliminate the seeking or taking of bribes, there are hopes that a uniform set of rules will curtail corrupt behavior, as long as those rules are both enforceable and enforced.